Karyotype of Four Mouth-Brooding Betta Fishes (Betta Bleeker, 1850) in Thailand - Sarasan, Teamjun; Supiwong, Weerayuth; Sriwattanarothai, Namkang; Panijpan, Bhinyo; Srisamoot, Nattapong; Tanomtong, Alongklod (Food Agricultural Sciences and Technology, 2021)
The karyotype and chromosomal characteristics of nucleolar organizing regions (NORs) of four mouth-brooding Betta from Thailand: Betta pi Tan, 1998, B. prima Kottelat, 1994, B. pugnax (Cantor, 1849), and B. simplex Kottelat, 1994, were reported. The results exhibited that the diploid chromosome number (karyotype formula) and fundamental number (NF) of each species are; B. pi, 2n=34 (4m+4sm+18a+8t) NF=60, B. prima, 2n=38 (6m+12a+20t) NF=56, B. pugnax, 2n=40 (4m+2sm+14a+20t) NF=60 and B. simplex, 2n=46 (2m+2sm+4a+38t) NF=54. All species revealed one pair of NOR-bearing chromosomes located on the short arm (p) of the acrocentric chromosome. In addition, the different sizes and morphology of Ag–NOR were observed in these four Betta fishes.